Parent transmit happiness along with associated values and behaviors to their children: A lifelong happiness divided? - Bruce Headey; Ruud Muffels; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
There are strong two-way links between parent and child happiness (life satisfaction), even for children who have grown up, moved to their own home and partnered themselves. German panel evidence shows that transmission of (un)happiness from parents to children is partly due to transmission of values and behaviors known to be associated with happiness (Headey, Wagner and Muffels, 2010, 2012). These values and behaviors include giving priority to pro-social and family values, rather than material values, maintaining a preferred balance between work and leisure, active social and community participation, and regular exercise. Both parents have about equal influence on the values and behaviors which children adopt. However, the life satisfaction of adult children continues to be directly influenced by the life satisfaction of their mothers, with the influence of fathers being only indirect, via transmission of values and behaviors. There appears to be a lifelong happiness dividend (or unhappiness dividend) due to parenting.
Keywords: 330; life satisfaction; inter-generational transmission; German panel survey (SOEP); Zufriedenheit; Familiensoziologie; Generationenbeziehungen; Schätzung; Deutschland